Preventive effect of yuzu and hesperidin on left ventricular remodeling and dysfunction in rat permanent left anterior descending coronary artery occlusion model. - Hye Yon Yu; Ji Hun Ahn; Se Won Park; Yi-Sook Jung (PLoS ONE, 2015)
Left ventricular (LV) remodeling, which includes ventricular dilatation and increased interstitial fibrosis after myocardial infarction (MI), is the critical process underlying the progression to heart failure. Therefore, a novel approach for preventing LV remodeling after MI is highly desirable. Yuzu is a citrus plant originating in East Asia, and has a number of cardioprotective properties such as hesperidin. However, no study has proved whether yuzu can prevent LV remodeling. The aim of this study was to determine the effects of yuzu on heart failure (HF) and its potential impact on the LV remodeling process after MI. Our in vivo study using the permanent left anterior descending coronary artery (LAD) occlusion model demonstrate that one week pre-treatment with yuzu or its major metabolite hesperidin before LAD occlusion significantly attenuated cardiac dysfunction, myocyte apoptosis and inflammation. Not only yuzu but also hesperidin inhibited caspase-3 activity, myeloperoxidase expression, α-smooth muscle actin expression, and matrix metalloproteinase-2 activity in a permanent LAD occlusion rat model. To our knowledge, our findings provide the first evidence that yuzu and hesperidin prevent MI-induced ventricular dysfunction and structural remodeling of myocardium.